Study on the Stiffness Correction Method of Novel Antivibration Bearing for Urban Rail Transit Viaduct - Weiping Xie; Youfu Du; Liangming Sun; Agostino Marioni; Xu Liang (Shock and Vibration)
A novel antivibration bearing is developed to reduce the train-induced vibrations for urban rail transit viaduct. It adopts four high-damping thick rubber blocks stacking slantingly to reduce the vibration and provide large lateral stiffness. But the existing stiffness calculation method of laminated rubber bearing aimed at horizontal seismic isolation is unsuitable for thick rubber bearing designed for vertical vibration reduction. First, the stiffness correction method has been proposed based on the characteristics of the novel bearing. Second, to validate the design method, mechanical property tests are performed on a specimen of the novel bearing with design frequency at 8 Hz and with 3500 kN bearing capacity. Third, damping effects of the novel bearing are investigated through impulse vibration tests on scaled models. Results show that the mechanical property of the novel bearing can satisfy the engineering demand, and the proposed method for calculating the stiffness agrees well with the test results. The overall insertion loss of the novel bearing is 13.49 dB which is 5.32 dB larger than that of steel bearing, showing that the novel bearing is very promising to be used in the field to mitigate train-induced vibrations.